ANALYSIS OF THE ERADICATION OF THE FREE PAPUA ORGANIZATION BY THE TNI-POLRI APPARATUS IN KOMPAS.COM'S SOCIAL MEDIA FRAMING - Zulkifli (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to determine the analysis of the eradication of the Papua Merdeka Organization by the TNI-Polri Apparatus in the framing of Kompas.com social media. The theory used is the Social Construction of Peter L. Berger and Thomas Luckmann. This study uses a constructivist paradigm and a qualitative approach. Qualitative approach. The research method used is a descriptive qualitative method using a literature study. The results of the study indicate variations in the framing of the OP M conflict in Papua by social media. Some media provide different views; some provide support to the TNI-Polri in the OPM eradication operation, while others provide views on the many cases of crime committed by the Armed Criminal Group (KKB), most of whose victims died. This finding indicates a difference in approach in reporting conflicts that can influence public perception in the conflict. The results of this study are the importance of awareness of the discussion and views used by the mass media in reporting on conflicts and acts of violence and the need for analysis of news received by the public in order to understand the broader context of the Eradication of the Papua Merdeka Organization by the TNI-Polri Apparatus.